Comparison of infrazygomatic crest bone screw position using a postero-anterior cephalogram versus cone-beam computed tomography: a cross sectional study - Ashfaq Sauni; Mathew Silju; Prashantha G.S; Sabrish Sharanya; Krishnamurthy Sathyashree; Bhaduri Nirajita (Sciendo, 2023)
The position of infrazygomatic crest bone screws is an important consideration in determining the success of orthodontic treatment. The aim of this study was to compare the position of infrazygomatic crest (IZC) bone screws in relation to skeletal and dental parameters using postero-anterior (PA) cephalograms and cone beam computed tomography (CBCT).